Insights into carbon recovery from excess sludge through enzyme-catalyzing hydrolysis strategy: Environmental benefits and carbon-emission reduction. (May 2022) - Zou, Xiang; He, Junguo; Zhang, Pengfei; Pan, Xinlei; Zhong, Yijie; Zhang, Jie; Wu, Xuewei; Li, Biqing; Tang, Xia; Xiao, Xiannian; Pang, Heliang
Graphical abstract: Highlight: Adding lysozyme at 0 h and protease at 1 h with the ratio of 4:1 was the best. Dosing time was as essential as dosing ratio for pretreatment efficiency. Enzyme cocktails triggered more extracellular biodegradable organic substances. Lysozyme and protease cocktail enhanced hydrolysis synergistically. Enzymatic sludge reduced carbon emission in place of methanol as carbon source. Abstract: This study introduced the excellent improvement of enzyme cocktail (lysozyme and protease) on hydrolysis efficiency and the role of reducing carbon emission as an alternative carbon source. The best dosing method after optimization was to add four parts of lysozyme at 0 h and one part of protease at 1 h. The extracellular proteins and polysaccharides increased by 118% and 64% respectively under the optimal dosing mode. Enzyme cocktails reduced more organic matters and extended the distribution of sludge particles in the small particle size part. The enzymatic-treated sludge could reduce 21.09 kg CO2 /t VSS if utilized to replace methanol for denitrification carbon source. Enzyme cocktails did better in enhancing both solubilization and hydrolysis than single enzymes under the optimal method. This study will provide a more integrated and comprehensive system for enzymatic pretreatment and new insight into the enzymatic pretreatment enhancing hydrolysis and reducing carbon emission.